2018
DOI: 10.18203/2349-3933.ijam20182489
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between glycemic control markers and lipid profile in type 2 diabetes mellitus and impaired glucose tolerance

Abstract: Background: Many studies have compared and correlated glycemic control markers with lipid profile in type 2 diabetes mellitus (T2DM) patients, but very few studies correlate them in impaired glucose tolerance (IGT) individuals. Thus, the aim of this study was to find comparison and correlation between FBG, PPBG and HbA1c with lipid profile in T2DM patients and IGT individuals.Methods: The study was conducted at tertiary care hospital in north Karnataka. The diagnosis of T2DM and IGT was based on WHO criteria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(29 reference statements)
2
4
0
Order By: Relevance
“…In our study we observed significantly high FBS and HbA1c in hyperglycemic patients (pre-diabetic and diabetic) compared to controls. Our result was consistent with that of Shrestha S et al [11] and Birader SB et al [12].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study we observed significantly high FBS and HbA1c in hyperglycemic patients (pre-diabetic and diabetic) compared to controls. Our result was consistent with that of Shrestha S et al [11] and Birader SB et al [12].…”
Section: Discussionsupporting
confidence: 94%
“…High HbA1c level indicates poor glycemic control that significantly increases the risk of atherovascular diseases [5]. HbA1c implicates the glycemic status of over previous [8][9][10][11][12] weeks and thus serves as a useful indicator of diabetes progression and onset of its complications [6]. Not only in diabetic patients, HbA1c also acts as marker of CVD in healthy individuals too [7].…”
Section: Introductionmentioning
confidence: 99%
“…Dyslipidemia makes diabetics prone to heart disease (CHD and other atherosclerosis complications). Our result concurrent with Sultania S et al (18) , Bhambhani GD et al (19) & Biradar SB et al (20) .…”
Section: Methodssupporting
confidence: 91%
“…Biradar SB et al 2018 (20) the study T2DM patients showed significant increases in TGL and VLDL serum, further the study showed increases in TC and LDL levels that were not statistically significant compared to normal healthy control group. T2DM patients experienced a significant decrease in HDL compared to the normal control group.…”
Section: Result: Graph 1: Showing Age Group Wise Distribution Of T2dmmentioning
confidence: 89%
“…Increase in the serum levels of the hepatic enzymes may lead to reduced concentrations of total protein (TP) and albumin in the serum [7]. Poor glycaemic control during diabetes mellitus causes hyperlipidaemia, which is associated with an increased flux of free fatty acid due to insulin resistance [8,9].…”
Section: Introductionmentioning
confidence: 99%